Pharmacy Students’ Over-the-counter Recommendations for Primary Dysmenorrhea and Childhood Fever Cases in an Indonesian University - Brata, Cecilia; Wibowo, Yosi Irawati; Natasya, Priscilia Amanda; Setyaningrum, Krysnadewi; Halim, Steven Victoria; Setiawan, Eko; Sunderland, Brucce (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: The quality of pharmacy education is stated in the literature to be one of the factors influencing the quality of self-medication services in pharmacies. However, research describing the ability of pharmacy students to handle self-medication cases is limited.Objectives: This study aims to describe pharmacy students’ recommendations for two vignette cases involving analgesic-antipyretics (i.e., primary dysmenorrhea and childhood fever cases) in an Indonesian university and to identify factors related to the appropriateness of their recommendations.Methods: Apothecary students were asked to provide recommendations and their reasoning for primary dysmenorrhea and childhood fever cases using a structured telephone interview.Results: Of the 86 participants, appropriate recommendations were provided by 86% and 78% for a case of primary dysmenorrhea and for childhood fever respectively. One-quarter of students did not identify referral criteria in the case of childhood fever and thus made inappropriate recommendations. Age and study period were factors significantly related to providing appropriate recommendations, in which students who were younger and completed their study program within 5 to 6 years were significantly able to provide appropriate recommendations compared to students who were older and whose study period exceeded 6 years.Conclusion: A considerable number of apothecary students in an Indonesian university were able to properly manage cases related to analgesic-antipyretic recommendations. Further qualitative research is needed to identify factors underlying the knowledge of Indonesian pharmacy students in identifying major and minor patient presentations.